The Berenstain Bears accept no substitutes - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923- (New York : Random House, 1993)
When a new substitute teacher comes to Bear Country School, the cubs learn that appearances can be deceiving.
"RL: 2.5"--Cover p. [4].
530
530
Accelerated Reader AR
Keywords: Schools -- Juvenile fiction; Substitute teachers -- Juvenile fiction; Bears -- Juvenile fiction; Conduct of life -- Juvenile fiction